SUSTAINABILITY OF PENSION SYSTEMS AND INTERESTS OF THEIR PARTICIPANTS - Azguridienė, Guoda (Politologija, 2015)
The article analysis motivations and expectations of pension systems’ participants. The major question is what goals of pension systems are viable or what are the correct indicators to measure success of pension systems. The question strives from the fact that modern societies raise very ambitious tasks for their pension systems and are not successful in implementing them. The hypothesis is that behind visible shortages of pension systems, that are well known and researched, there are deeper, fundamental reasons causing inner contradictions of these systems. They are due to human nature – to seek for own interest. The article argues that without solving this inner contradiction, pension systems can not become viable and beneficial for societies. Today’s political decisions are predominantly influenced by economic thoughts based on experimental principles and statistical data calculations. Human motive is not considered to be essential. Contrary to this, Austrian economic school places the acting man at the centre of all economic matters. According to this theory, all social systems have to function in the way that allows different participants to fulfil their interests and cooperate. Otherwise conflicting interests create inner tensions in the system and do not allow it to function effectively. There are three groups of the pension system’s participants defined in the article: pensioners (receivers), work force and business (contributors) and politicians (decision makers). Primary interest and fair expectation of a pensioner is to receive his pension. If this is fulfilled, he wishes bigger pension, earlier retirement or similar value increase. The expectations of pensioners are reasonable from their point of view but limitless, therefore not reasonable from the society’s point of view. This conflict can be avoided only if retirement conditions are well defined. In order not to have void expectations people have to understand realistic benefits while contributing to pension system. However present set up of public pensions excludes this possibility totally. Unrealistic and ever increasing expectations of pensioners, that put the pressure on politicians and public finances and ultimately ruin pension systems, are determined by PAYGstructure itself. The other group of participants – working population – that supply PAYGpension systems with funds has the interest to contribute as less as possible. From the point of view of the employee, at least in Lithuania, pension contribution is hardly considered his own input in future pension because weak connection between contribution and allowance, weak trust in government, fact that contribution is paid by the employer and etc. Even if considered own, being future benefits most often are low in priority (due to time preference). Bearing in mind the fact that contributions are obligatory and do not allow any flexibility in payment, the only reasonable interest is to minimize them. Such interest for the employer is even stronger. Pension contribution is a substantial financial and administrative burden which brings no added value, because employee doesn’t treat it as part of his salary, but as the employers tax. For motivation purposes employer has other much more efficient tools, however can not chose between them and PAYG, because the latter is mandatory. The third interest group in pension system is the decision maker – political parties and individual politicians. It is not so obvious that their interest is to preserve PAYGrunning – when a big part of public finance problems are caused by it. However structural pension reforms, needed to eliminate its inner conflict, require decisions that offend short term interests of possibly big part of population. The benefits of structural reform come up in long run and are dispersed among different groups. This does not motivate politicians to introduce structural changes. The article concludes that first of all it is very important to realize interest contradictions of pension system participants as well as to stop describing public pension system as life-time income guarantee. Such guaranty can not be created both in general (due to nature of our existence) and in particular by mandatory public means (due to inherent inefficiency of such undertakings). However, while public demand for social security illusion exists and it fits well with political interests, the only pragmatic trend is one propagated by Word Bank – to increase pension scheme diversification that makes PAYGpillar less dominating. It shall be gradually replaced by the schemes, where choice is established instead of obligation and individual, family or unenforced community is approached instead of statistical unit of population.